2020
DOI: 10.1159/000509714
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miRNA-451a Promotes the Differentiation of CD4+ T Cells towards Th2 Cells by Upregulating ETS1 in Childhood Asthma

Abstract: Children exposed to common aeroallergens may develop asthma that progresses into adulthood. Inflammation regulated by T helper 2 (Th2) cells, a specific subpopulation of CD4+ T lymphocytes, is involved in asthmatic injury. Herein, our microarray data indicated that microRNA-451a-5p (miRNA-451a) expression decreased by 4.6-fold and ETS proto-oncogene 1 (ETS1) increased by 2.2-fold in the peripheral blood lymphocytes isolated from asthmatic children (<i>n</i> = 4) as compared to control individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…miRNA play a crucial role in a variety of biological processes. In the past years, a great number of studies have also shown that miRNA plays a crucial influence in airway inflammation and airway smooth muscle cell proliferation in asthma ( 9 , 10 ). Our previous studies found that miR-23b inhibited the cell proliferation of airway smooth muscle cells ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA play a crucial role in a variety of biological processes. In the past years, a great number of studies have also shown that miRNA plays a crucial influence in airway inflammation and airway smooth muscle cell proliferation in asthma ( 9 , 10 ). Our previous studies found that miR-23b inhibited the cell proliferation of airway smooth muscle cells ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In childhood asthma, miRNA-451a was found to inhibit Th2 cell differentiation by down-regulating protooncogene 1 (ETS1). This study reveals that miRNA-451a-ETS1 axis dysfunction is a novel molecular mechanism that underlies the pathogenesis of childhood asthma [40]. A study has shown that miR-1165-3p targets IL-13 and PPM1A to control Th2 differentiation and pulmonary inflammation in asthma.…”
Section: Mirnas Regulation Of Th2 Differentiation Via Signaling Pathwaysmentioning
confidence: 84%
“…The inflammatory mediators in asthma have been extensively studied for their roles in cell recruitment and cell activation [ 20 , 21 , 58 ]. We also quantified a number of cytokines in the BAL from the mice and found that WT OVA mice had significantly higher concentrations of IL-4, IL-5, IL-6, IL-13, and CXCL1 compared to the Lsp1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effective treatment for the 5–10% of cases that comprise severe asthma account for bulk of the asthma-related healthcare costs [ 19 ]. Inflammatory mediators such as IL-4, IL-13 and CXCL1 have important regulatory roles in asthmatic cell recruitment and activation [ 20 , 21 ]. It appears that excessive migration of neutrophils and eosinophils may underlie the inflammation-associated structural and physiologic changes in the asthmatic lung.…”
Section: Introductionmentioning
confidence: 99%